Pengaruh Metode Tutor Sebaya Pada Pembelajarn Tari Begambo di SMA Negeri 2 Babat Toman - Zaina Fitriyani; Efita Elvandari; Hasan Hasan (Imajinasi : Jurnal Ilmu Pengetahuan, Seni, dan Teknologi, 2024)
This research aims to find out whether the peer tutoring learning method influences the learning outcomes of begambo dance. This method is used in experimental research methods (one group pretest and posttest design). The subjects of this research were students in class X E 5 of SMA Negeri 2 Babat Toman. The samples were taken based on the criteria used by the researcher, so the samples were taken using a purposive sampling technique and obtained class X E 5 experimental classes. The data analysis used is the t-test, data collection using observation techniques, the work test is the implementation of the pretest and posttest and the supporting data collection is documentation. Based on data analysis, the research results show that the students' scores on the posttest are greater than the students' scores on the pretest. H_(0) is accepted if t_(count)≤t_tabel while t_(count) is 3.19 and t_tabel 1.98. So it can be said that there is an influence of the use of the peer tutoring method on Begambo dance learning at SMA Negeri 2 Babat Toman with the hypothesis testing criteria Hadi Accepted and H0 is rejected. This shows that there is an influence of the peer tutoring method on the value of learning outcomes of begambo dance in class X E 5 SMA Negeri 2 Babat Toman.